SCOLIOSIS CORRECTION IN ”C” LONG THE AGE OF 30-40 YEARS (GYMNASIUM, 2017)
Scoliosis is a condition wherein the backbone is cleared in the frontal plane (on one side). Backbone curve usually shaped ”S” or ”C”. Purpose of this study is to determine the best treatment for pain relief and spinal deviation to prevent aggravation of existing conditions by the appearance of intercostal neuralgia and herniated disc. The hypothesis of the study. It is assumed that scoliosis patients receiving appropriate therapy can improve spinal mobility and may relieve back pain both methods chiropractic, massage and electrotherapy and by adopting correct postures and attitudes. For patients studied is recommended cardiovascular exercises, exercises to strengthen back muscles, thighs and knees, even aerobic exercise. It is advisable to carry at least 20 minutes per day for a walk, a jog, or ride a bicycle. Scoliosis patients receiving appropriate therapy can improve spinal mobility and may relieve back pain through chiropractic methods, massage and electrotherapy and by adopting correct postures and attitudes.